GIS-BASED REGRESSION ANALYSIS OF THE RELATIONSHIP BETWEEN ECOLOGICAL FOOTPRINT AND ECONOMIC DEVELOPMENT OF SELECTED COUNTRIES - Majid, M. Rafee; Zaman, Musarrat; Halim, Norhazliza (PLANNING MALAYSIA, 2018)
Ecological footprint is an innovative concept to present the consumption of natural resources and generation of waste in terms of the Earth biological carrying capacity in a standardized format. The Earth overall sustainability can also be measured with the idea of ecological footprint and bio-capacity. The aim of this paper is to analyse the interactive spatial relationship between economic development and ecological footprints of selected nations. The GIS-based spatial regression tool Ordinary Least Square (OLS) and Geographically Weighted Regression (GWR) are used for fulfilling the purpose. Individual components of ecological footprints - cropland, grazing land, fishing ground, forest land, builtup land and carbon footprints - are also analysed against the per capita GDP of the nations in order to understand the interrelationship between them. The analysis has found a significant relationship between ecological footprint and economic development and the OLS model can explain approximately 64% of the variation in the dependent variable with the explanatory variables. The study has also found that nation’s economic development contributes much in increasing the carbon footprint. The resulted outcome is significant enough to warrant a study on the spatial dimension of environment and economy in order to analyse the individual nation’s economic growth and its relationship with environmental degradation, which can ultimately influence the global environmental sustainability